ANALISIS PELAKSANAAN DETEKSI DINI GANGGUAN JIWA DI PUSKESMAS BANYUURIP KABUPATEN PURWOREJO - Syafira Risdanti; Septo Pawelas Arso; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Physical health problems that are often left unattended are often cases of mental illness and suicide. Early detection includes targeted prevention. Early detection of mental disorders is for the productive age and old age. Puskesmas Banyuurip carries out early detection of mental disorders in community-based mental health services. Implementation involves elements of the community. While planning by the Puskesmas. This research is a qualitative research with a descriptive approach with in-depth interview method. This research was conducted in February-April 2020. Informants were key informants and triangulation informants. The aspects analyzed include input, process, and product. The input aspect shows that there are limited staff and funds but this is an opportunity in planning, namely the development of cadres and the use of non-government funds. This aspect of the process shows a lack of implementation in education and referrals so there is a need for supporting facilities. The product aspect is responded to by a 100% target as a must. Achievements in 2019 will be an improvement in the implementation of the next period. Kader can be trained with early detection training on classification methods. Comprehensive education for all targets requires a cross-sectoral role. The Health Department can improve coordination with other sectors as well as the private sector.